Critical period of weed competition in direct seeded rice under saturated and flooded conditions - Juraimi, Abdul Shukor; Mohd Yusof, Mohamad Najib; Begum, Mahfuza; Abd Rahim, Anuar; Man, Azmi; Puteh, Adam (Universiti Putra Malaysia Press, 2009)
Field experiment was conducted at the Malaysian Agriculture Research and Development Institute (MARDI) station, Seberang Perai, Penang in off-season 2005 and main season 2005/2006, to determine the critical period of weed competition in saturated and flooded conditions. The experiment consisted of different seasons, namely weed free and no weeding periods. Sum Dominance Ratio showed that the weed compositions were different in the saturated condition, as compared to the flooded condition for both seasons. The dominance ranking of weed groups in the off- season in 2005 in saturated condition was sedges, followed by grasses and broadleaved, while during the main season of 2005/2006, grassy weeds were the most dominant, followed by sedges and broadleaved weeds. In the flooded condition, the dominance rankings of weed groups (such as broadleaved>grass>sedges) were the same in both seasons. The number of tillers, along with rice grains yield, was significantly affected by the weed competition in both saturated and flooded conditions. Yield loss due to weed competition was higher in the saturated condition (54.5%) than in the flooded condition (35.2%). Based on the 5% level of yield loss, the critical period in the off-season of 2005 was between 2-71 days, after sowing (DAS) in saturated condition, and 15-73 DAS in flooded condition. Meanwhile in the main season of 2005/2006, the critical period was between 0-72 DAS in the saturated condition and 2-98 DAS in the flooded condition.